Tigecycline-induced sustained severe hypoglycemia: a case report - Yixin Chen; Lin Li; Nan Zhang; Hong Li (BMC, 2019)
Abstract Background Tigecycline, the first glycylcycline-class drug, is a broad-spectrum antibiotic with activity against multi-drug resistant (MDR) organisms. We describe a case of sustained and severe hypoglycemia in a patient treated with tigecycline for pneumonia due to MDR Klebsiella pneumoniae. Case presentation A 74-year-old man was admitted for treatment of pneumonia. At admission he had prediabetes. In the hospital he developed renal failure. On day 3, the patient experienced severe shortness of breath. He was intubated and transferred to the intensive care unit (ICU) for ventilator support. In the ICU the antibiotic regimen was cefoperazone and sulbactam (1 g every 12 h). Continuous Renal Replacement Therapy was started on that day. Test for anti-neutrophil cytoplasmic antibodies (ANCA) was positive, and so the nephrologist and rheumatologist agreed on a diagnosis of ANCA-associated vasculitis, with renal and pulmonary involvement and acute renal failure. Plasmapheresis, and high-dose methylprednisolone treatment were started on day 6, and there was obvious improvement in the patient's condition. The steroid regimen was gradually tapered to oral prednisone (35 mg every day) on day 19. Afterwards, the patient's pneumonia worsened. Sputum culture showed Klebsiella pneumoniae sensitive to only tigecycline. Tigecycline treatment (100 mg every 12 h) was administered on day 20. Hypoglycemia started about 37 h after the first dose of tigecycline. Infusion of 50% glucose through the femoral vein was required for over 20 h to maintain normal blood glucose concentrations. Tigecycline was stopped, but the hypoglycemia resolved only after a further 34 h. The insulin and C-peptide levels were found to be markedly elevated during the hypoglycemia. The Naranjo scale score of 7 indicated that the likelihood of tigecycline causing severe hypoglycemia was "probable." Conclusion This is the first report of sustained severe hypoglycemia due to tigecycline. Oversecretion of insulin appears to have been the cause of the hypoglycemia in our patient. The mechanism needs to be investigated.